“Cops Need Doxxed”: Releasing Personal Information of Police Officers as a Tool of Political Harassment - Huey, Laura (Crime & delinquency, 2025)
The present study explores the phenomenon of doxxing and, in particular, the use of doxxing as a form of harassment against police officers. This work relies on an analysis of in-depth interviews with 65 (n = 65) police officers from across Canada, each of whom has had experiences of policing politically contested events. Drawing on our data, we outline specific examples of the doxxing of police officers, before exploring the political and other impacts on both police agencies and individual officers. We conclude with a discussion of the need for police and policymakers to begin considering the need for potential changes to policy and practice in order to protect workers from off-duty harassment.